2006
DOI: 10.1021/ja063939e
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneously Alloyed CdSxSe1-x Nanocrystals:  Synthesis, Characterization, and Composition/Size-Dependent Band Gap

Abstract: Alloy nanocrystals provide an additional degree of freedom in selecting desirable properties for nanoscale engineering because their physical and optical properties depend on both size and composition. We report the pyrolytic synthesis of homogeneously alloyed CdS(x)Se(1-x) nanocrystals in all proportions. The nanocrystals are characterized using UV-visible absorption spectroscopy, transmission electron microscopy, X-ray diffractrometry, and Rutherford backscattering spectrometry to determine precisely structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

33
283
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(318 citation statements)
references
References 80 publications
33
283
2
Order By: Relevance
“…37,38 The calculated curves (solid lines) agree well with the experimentally observed data (dots). Differences between the observed and calculated data were less than, or comparable to, ∼100 meV.…”
Section: A Applicability Of Finite-depth-well Ema Calculation To Allsupporting
confidence: 81%
See 2 more Smart Citations
“…37,38 The calculated curves (solid lines) agree well with the experimentally observed data (dots). Differences between the observed and calculated data were less than, or comparable to, ∼100 meV.…”
Section: A Applicability Of Finite-depth-well Ema Calculation To Allsupporting
confidence: 81%
“…In general highly monodisperse colloidal QDs are easier to synthesize with diameters in the range of 3-6 nm. [37][38][39][40] This suggests that the target compositions for Zn(Te 1 x Se x ) alloyed QDs are 0.02≤x≤0.68 for green emission and 0≤x≤0.06 and 0.66≤x≤0.9 for blue emission. In the Zn(Te 1 x S x ) alloy system, those are 0.26≤x≤0.37 for red emission, 0.01≤x≤0.2 and 0.45≤x≤0.61 for green emission and 0≤x≤0.02 and 0.63≤x≤0.72 for blue emission.…”
Section: A Applicability Of Finite-depth-well Ema Calculation To Allmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5 As an additional degree of freedom in varying the chemical composition of chalcogenide-based materials, more than one chalcogenide species can be present in the lattice, for example S and Se. To date, several colloidal NCs of mixed metal ''sulfides-selenides'' have been reported, for example HgS y Se 1Ày , 6 ZnS y Se 1Ày , 7 SnS y Se 1Ày , 8 CdS y Se 1Ày , 9 PbS y Se 1Ày , 10 CuIn-(S y Se 1Ày ) 2 , 11 Cu x Fe 4 Sn 12 (S y Se 1Ày ) 32 12 and Cu 2 ZnSn(S y Se 1Ày ) 4 . 13 On the other hand, the ability to control the crystal phase and to obtain NCs in phases that were previously non-accessible is also quite relevant (see for example recent works on wurtzite Cu 2 ZnSnSe 4 and Cu 2 ZnSnS 4 NCs).…”
Section: Introductionmentioning
confidence: 99%
“…Swafford et al reported that the composition of the CdS x Se 1Àx nanoalloys remained reasonably constant over the growth period for all the Se : S ratios, establishing the homogenous nanoalloy. 12 Ouyang et al also suggested the formation of the homogenous nanoalloys.…”
mentioning
confidence: 98%